Uplink from the underground - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 2002)
The young Tribulation Force, a group of teens left behind on Earth after God's Rapture, continue their attempts to lead others to the truth in spite of continuing assaults from the evil Global Community.
"Showtime for Vicki"--Cover.
"Tyndale Kids.".
5.6
5-8
Keywords: Christian fiction; Eschatology -- Fiction; Fantasy; Schools -- Fiction; Teenagers -- Fiction; Christian fiction; Eschatology -- Fiction; School stories; Teenagers -- Fiction; Fantastic fiction